Place Attachment Masyarakat di RW 04, Kelurahan Polehan, Kota Malang - Efma Haryani; Wara Indira Rukmi; Deni Agus Setyono (Diponegoro University, 2021)
The settlement area in RW 04 is determined as one of the priority areas that the Government of Malang City should overcome from slum problems. Slum factors in RW 04 are caused by density settlement, unlivable residential area, and environmental pollution by the community activities. Therefore, the local government creates a program to diminish the slum and to support the 100-0-100 Program as well. The effort to overcome the slum problems is done through a progam called PLPBK (Penataan Lingkungan Permukiman Berbasis Komunitas) which can affect community place attachment. Hence, the community image of RW 04 would change from a slum into a clean and beautiful residential area. The environmental transformation in RW 04 could strengthen place attachment and as a result, the people feel more comfortable, proud, and safe. This study aims to identify community place attachment in RW 04, Polehan, Malang and the analysis used is descriptive statistics. This research shows that the community would have a strong place attachment as long as the respondents have the willingness to develop place attachment through experience, intensity of social interaction, the possession of valuable object, action or effort to control the environment, the length of resident, do not migrate, and RW 04 that is able to replace the childhood memories of immigrant. The strong place attachment is affected by the respondents characteristics as well, and as a result, they tend to have willingness to live in RW 04.